Diferencias teóricas y prácticas de la información y de la comunicación - Vera Vera, Héctor (Re-presentaciones: Periodismo, comunicación y sociedad, 2006)
In spite of the fact that information and communication are different concepts, in practice, and even in the specialized treatises, they are confused. In everyday life, indeed, they are mixed, but this non-theoretical distinction leads to grave mistake of diagnosis and planning. Both phenomena should be tacklad from different epistemological foundations to detect their specifics. In this article we try to demonstrate that they structural aspects of information belong to, or are closer to, the general theory of systems, and the themes of meaning belong to phenomenology and the social sciences.